Cisgender male and transgender female sex workers in South Africa: gender variant identities and narratives of exclusion. Issue 1 (2nd January 2016) - Samudzi, Zoe; Mannell, Jenevieve
Abstract: Sex workers are often perceived as possessing 'deviant' identities, contributing to their exclusion from health services. The literature on sex worker identities in relation to health has focused primarily on cisgender female sex workers as the 'carriers of disease', obscuring the experiences of cisgender male and transgender sex workers and the complexities their gender identities bring to understandings of stigma and exclusion. To address this gap, this study draws on 21 interviews with cisgender male and transgender female sex workers receiving services from the Sex Workers Education and Advocacy Taskforce in Cape Town, South Africa. Our findings suggest that the social identities imposed upon sex workers contribute to their exclusion from public, private, discursive and geographic spaces. While many transgender female sex workers described their identities using positive and empowered language, cisgender male sex workers frequently expressed shame and internalised stigma related to identities, which could be described as 'less than masculine'. While many of those interviewed felt empowered by positive identities as transgender women, sex workers and sex worker-advocates, disempowerment and vulnerability were also linked to inappropriately masculinised and feminised identities. Understanding the links between gender identities and social exclusion is crucial to creating effective health interventions for both cisgender men and transgender women in sex work.